Post-CABG Deep Sternal Wound Infection: A Retrospective Comparative Analysis of Early versus Late Referral to a Plastic Surgery Unit in a Tertiary Care Center - Sahasrabudhe, Parag B.; Pradhan, Mugdha D.; Panse, Nikhil; Jagtap, Ranjit (Indian Journal of Plastic Surgery, 2021)
Background Deep sternal wound infections (DSWI) following median sternotomy are initially treated by the cardiothoracic surgeons and are referred to a plastic surgical unit late in the course of time.Methods This is a retrospective review done in a tertiary care teaching institute from January 2005 to June 2018 and the data of 72 patients who had DSWI out of 4,214 patients who underwent median sternotomy for coronary artery bypass grafting (CABG) was collected with respect to the duration between CABG and presentation of DSWI as well as time of referral to a plastic surgery unit. We defined early referral as < or equal to 15 days from presentation and late referral as > 15 days. Both groups were compared with respect to multiple parameters as well as early and late postoperative course, postoperative complications, and mortality.Results The early group had 33 patients, while the late group had 39 patients. The number of procedures done by the cardiothoracic team before referral to the plastic surgery unit is significant (p = 0.002). The average duration from the presentation of DSWI to definitive surgery was found to be 16.58 days in the early group and 89.36 days in the late group. The rest of the variables that were compared in both the groups did not have significant differences.Conclusion There is no statistical difference between early and late referral to plastic surgery in terms of mortality and morbidity. Yet, early referrals could lead to highly significant reduction in total duration of hospital stay, wound healing, and costs. Early referral of post-CABG DSWIs to Plastic surgeons by the cardiothoracic surgeons is highly recommended.
Keywords: deep sternal wound infection (DSWI); negative pressure wound therapy; omental flap; pectoralis major muscle flaps; sternal dehiscence